(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
This article discusses a detailed talk of programs that allow the opportunity to mathematical and physical modeling. Also, the concepts and functions of modeling, and students in the education of staem are given special forms and techniques to organize research to create physical or mathematical models by integrating the theoretical and practical knowledge.